The Impact of Companies' Financial Results on Investors' Financial Decisions During The COVID-19 Pandemic in Selected Companies Listed on The Warsaw Stock Exchange (WSE) - Mariusz CHMIELEWSKI; Maciej Leszek HYZY; Ewa SPIGARSKA (Communications of International Proceedings, 2023)
Positive financial results achieved by enterprises should improve market indicators, while negative financial results should affect the deterioration of market indicators. It is important from the point of view of the topic to examine the following hypothesis: There is a significant statistical relation between the net profit and the share price for IT and banking companies listed on the stock exchange; There is no significant statistical relation between the RoA indicator and the price to the book value for IT and banking companies; There is no significant statistical relation between the RoE indicator and the price to the book value for IT and banking companies. The statistical method is used in the article – it examines the correlation of financial results (net profit indicators: ROE, ROA) and market results (share price, share price to book value ratio) of companies listed on WSE for companies operating in the sector for which the crisis was an opportunity (companies from the IT sector) and companies from the banking sector. The correlation of selected financial and market indicators of companies from the IT sector and companies from the banking sector was examined.  The research shows that for most of the analysed entities listed on WSE, there is no statistically significant relation between financial parameters and their market parameters. When making investment-related decisions, stock exchange investors are only slightly guided by the financial results achieved by the analysed stock exchange companies – this applies to companies operating in the IT sector and the banking sector.
Keywords: financial and market indicators; COVID-19 crisis and pandemic; IT industry; financial industry JEL: G01; G11; M21; M29; M49; O16